2021
DOI: 10.3389/fcell.2020.622393
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Acute Lymphoblastic Leukemia Identified the Methylation and Expression Differences Between BCP-ALL and T-ALL

Abstract: Acute lymphoblastic leukemia (ALL) as a common cancer is a heterogeneous disease which is mainly divided into BCP-ALL and T-ALL, accounting for 80–85% and 15–20%, respectively. There are many differences between BCP-ALL and T-ALL, including prognosis, treatment, drug screening, gene research and so on. In this study, starting with methylation and gene expression data, we analyzed the molecular differences between BCP-ALL and T-ALL and identified the multi-omics signatures using Boruta and Monte Carlo feature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Increased gene expression of this gene can activate the pro-survival phosphatidylinositol-3-OH kinase pathway [100]. Recently, another study also analyzed molecular differences between B-ALL and T-ALL and found VPREB3 as a methylation and expression signature gene [101]. EBF1 is a transcription factor involved in B-cell lineage specification and commitment [102], which explains its increased expression in B-ALL compared to T-ALL ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased gene expression of this gene can activate the pro-survival phosphatidylinositol-3-OH kinase pathway [100]. Recently, another study also analyzed molecular differences between B-ALL and T-ALL and found VPREB3 as a methylation and expression signature gene [101]. EBF1 is a transcription factor involved in B-cell lineage specification and commitment [102], which explains its increased expression in B-ALL compared to T-ALL ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A subset of these markers has also previously been implicated in differences between B- and T-ALL. For example, LINC00114 and CCN2 have previously been found to be upregulated in B-ALL compared to T-ALL while deletions of EBF1 have been associated with B-ALL [102,103] and VPREB3 has been found as a methylation and expression signature gene between B- and T-ALL [101]. Comparing the different biotypes of the predicted markers, the protein-coding genes are described the most in literature.…”
Section: Discussionmentioning
confidence: 99%
“…HLA genes are involved in differentiating self- and non-self- cells in tumors and are candidate genetic susceptibility loci for childhood ALL. It has been reported that the HLA-DRA and HLA-DQB1 genes are associated with the progression of childhood ALL [ 41 , 42 ], and elevated HLA-DM expression contributes to childhood ALL [ 43 ]. CD molecules are commonly used as cell markers to define cells with certain functions or properties and to classify hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as a result of these studies, 7 expression signature genes and 175 methylation signature genes were obtained, in which two genes, including CD3D and VPREB3 were common. In addition, it has been implied that CD3D gene has a major regulatory contribution in the cell and molecular process of this type of cancer (Li et al, 2020).…”
Section: In Multi-omics Data Analyses Of Cancermentioning
confidence: 99%